2010
DOI: 10.1016/j.jcis.2009.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir films of flexible polymers transferred to aqueous/liquid crystal interfaces induce uniform azimuthal alignment of the liquid crystal

Abstract: We reported recently that amphiphilic polymers can be assembled at interfaces created between aqueous phases and thermotropic liquid crystals (LCs) in ways that (i) couple the organization of the polymer to the order of the LC and (ii) respond to changes in the properties of aqueous phases that can be characterized as changes in the optical appearance of the LC. This investigation sought to characterize the behavior of aqueous-LC interfaces decorated with uniaxially compressed thin films of polymers transferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Because of their high sensitivity and rapid response with respect to orientation, small-molecule LCs are an attractive medium for detecting chemical/biochemical events occurring at an interface as a result of optical changes that can be viewed with the aid of a polarized optical microscopy [28][29][30][31]. An optical change can occur as a result of a change in orientation of the LCs from vertical to parallel alignments at the water/LC interface upon adsorption of biomaterials [32].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their high sensitivity and rapid response with respect to orientation, small-molecule LCs are an attractive medium for detecting chemical/biochemical events occurring at an interface as a result of optical changes that can be viewed with the aid of a polarized optical microscopy [28][29][30][31]. An optical change can occur as a result of a change in orientation of the LCs from vertical to parallel alignments at the water/LC interface upon adsorption of biomaterials [32].…”
Section: Introductionmentioning
confidence: 99%
“…16, 17, 19, 40, 56, 57, 59-61 Here we note that in biological membranes, many functions of the membrane result from the ability of the proteins and lipids comprising the membrane to reorganize in a manner that is dependent on interactions of these species within the membrane. 70, 71 In synthetic systems, it has been observed that interfaces at which lipids exhibit mobility can be used to form organized assemblies of proteins, including protein crystals.…”
Section: Approaches To Interfacial Design Of Lc Materials For Biologimentioning
confidence: 92%
“…The first approach involves the spontaneous adsorption of lipid from an aqueous dispersion onto the LC interface, 15, 16, 18, 23, 59 and the second involves the transfer of a Langmuir monolayer of lipid prepared at the surface of water onto the LC-aqueous interface using the Langmuir-Schaefer technique. 55, 60, 61 Below we review each of these methods for functionalization of LC interfaces, and then illustrate the utility of these tailored LC interfaces for reporting protein binding events.…”
Section: Approaches To Interfacial Design Of Lc Materials For Biologimentioning
confidence: 99%
“…Over incubation for 2 h, a monolayer of L-DLPC was laden at LC-aqueous interface and resulted in a complete anchoring transition from planar to homeotropic alignment ( Figure 5(d)). Aside from lipids [29,30], it has been shown that amphiphilic molecules, such as surfactants [31][32][33][34][35][36][37] and polymers [38][39][40][41] at these interfaces are strongly coupled to the ordering of the LCs, and the presence and organization of these molecules can be reported through changes in the optical appearance of the LCs. It was noted that LCs are fluid-like and possess mobility, combined with liquid crystallinity, assembling biological amphiphiles at the LC-aqueous interface promises a possibility for mimicking cell membrane, which is mobile and composed of a large amount of lipids in liquid crystalline phase.…”
Section: Lc-aqueous Interfacesmentioning
confidence: 99%